Augmented Reality Guided Osteotomy in Hallux Valgus Surgery. Issue 3 (14th September 2018) - Wirth, Stephan; Viehöfer, Arnd; Laurenz, Jaberg; Zimmermann, Stefan; Dennler, Cyrill; Fürnstahl, Philipp; Farshad, Mazda
Category: Bunion Introduction/Purpose: An optimal osteotomy angle can avoid shortening of the first metatarsal bone after hallux valgus surgery and therefore reduce the risk of transfer-metatarsalgia. Up to date the osteotomy is performed free-hand without guidance and is therefore prone to unwanted variability in accuracy. The purpose of the present ex-vivo study was to investigate whether overlaying a hologram (augmented reality, AR) would improve accuracy of the distal osteotomy during hallux valgus surgery. Methods: A polyamide foot skeleton was constructed based a CT scan of a cadaveric foot and covered with medical silicon soft tissue. Three different polyamide first metatarsals were inserted to simulate a light, moderate and severe hallux valgus deformity. Distal Osteotomies of the first metatarsals were performed by two surgeons with different levels of surgical experience each with (AR, n=15x2) or without (controls, n=15x2) overlay of a hologram depicting an angle of osteotomy perpendicular to the second metatarsal in the transverse plane. Subsequently, the deviation to the plumb line of the second metatarsal in the transverse plane of all 60 osteotomies angles were optically measured and statistically analyzed. Results: Overall, the AR-guided osteotomies were more accurate (4.9 ± 4.2°) compared to the freehand cuts (6.7± 6.1°) by tendency (p=0.2). However, while the inexperienced surgeon performed more accurate osteotomies with AR with a mean angle of 6.4± 3.5° compared to freehand 10.5 ± 5.5° (p=0.02), no significant difference was noticed for the experienced surgeon with an osteotomy angle of around 3° in both cases. Conclusion: This pilot-study suggests that augmented reality guided osteotomies can potentially improve accuracy during hallux valgus surgery, particularly for less experienced surgeons. However, clinical studies are needed to investigate the clinical benefit of augmented reality in hallux valgus surgery.